Th1 cells contribute to retinal ganglion cell loss in glaucoma in a VCAM-1-dependent manner - Chong He; Kun Peng; Xiong Zhu; Zuo Wang; Wenbo Xiu; Gao Zhang; Yang Chen; Chaonan Sun; Xiao Xiao; Donghua Liu; An Li; Yanping Gao; et al. (Journal of Neuroinflammation, 2024)
Abstract Glaucoma is a complex neurodegenerative disorder characterized by the progressive loss of retinal ganglion cells (RGC) and optic nerve axons, leading to irreversible visual impairment. Despite its clinical significance, the underlying mechanisms of glaucoma pathogenesis remain poorly understood. In this study, we aimed to unravel the multifaceted nature of glaucoma by investigating the interaction between T cells and retinas. By utilizing clinical samples, murine glaucoma models, and T cell transfer models, we made several key findings. Firstly, we observed that CD4+ T cells from glaucoma patients displayed enhanced activation and a bias towards T helper (Th) 1 responses, which correlated with visual impairment. Secondly, we identified the infiltration of Th1 cells into the retina, where they targeted RGC and integrated into the pro-inflammatory glial network, contributing to progressive RGC loss. Thirdly, we discovered that circulating Th1 cells upregulated vascular cell adhesion protein 1 (VCAM-1) on retinal microvessels, facilitating their entry into the neural retina. Lastly, we found that Th1 cells underwent functional reprogramming before reaching the retina, acquiring a phenotype associated with lymphocyte migration and neurodegenerative diseases. Our study provides novel insights into the role of peripheral CD4+ T cells in glaucoma pathogenesis, shedding light on the mechanisms underlying their infiltration into the retina and offering potential avenues for innovative therapeutic interventions in this sight-threatening disease. Graphical Abstract